Motor control in reaction-time vs self-paced movement : MEG study on movement-related cortical fields - Hautasaari, Pekka (2017)
Hautasaari, P. 2017. Motor control in reaction-time vs self-paced movement - MEG study on movement-related cortical fields. Sport and Exercise Medicine, Unit of Health Sciences, Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s Thesis in Sport and Exercise Medicine, 34 pages, 2 appendices.